The Influence of Influencer Marketing and Store Atmosphere on Purchase Decision through Purchase Intention as Intervening Variable : A Case Study on Café Consumers in Malang City - Khusnia, Rif’atul; Pratikto, Heri; Rahayu, Wening Patmi (Journal of Applied Business, Taxation and Economics Research, 2025)
This study investigates the influence of Influencer marketing and Store atmosphere on Purchase decision with Purchase intention as an intervening variable among café consumers in Malang City. Based on the Theory of Planned Behavior (TPB), the research aims to fill research gaps concerning the effects of these variables in the rapidly evolving context of digital marketing. The research employed Smart PLS SEM to analyze data from 385 respondents of Generation Z aged 12-27 years. The results indicate that Influencer marketing has a positive and significant impact on Purchase intention, though it does not directly affect Purchase decision. Conversely, Store atmosphere significantly influences both Purchase intention and Purchase decision among café consumers in Malang. Furthermore, Purchase intention acts as a significant intervening variable between Influencer marketing, Store atmosphere, and Purchase decision. These findings provide insights for café owners and marketing practitioners to consider effective strategies in enhancing the influence of store atmosphere and utilizing influencers to improve consumer purchase decisions